Photoisomerization-enhanced 1, 3-dipolar cycloaddition of carbon-bridged octocyclic azobenzene with photo-released nitrile imine for peptide stapling and imaging in live cells. Issue 29 (10th July 2020) - Deng, Jiajie; Wu, Xueting; Guo, Guiling; Zhao, Xiaohu; Yu, Zhipeng
Abstract : A novel photo-click ligation reaction between nitrile imines and photo-switchable octocyclic azobenzenes was established to both tune the conformation of the NoxaB peptide and conjugate probes with enhanced efficacy in cell apoptosis. Abstract : A photo-induced 1, 3-dipolar cycloaddition between nitrile imine and highly ring-strained NN double bond as a dipolarophile was discovered. The photo-isomerization of carbon-bridged octocyclic azobenzene (CBOA) into its trans -configuration accelerates the ligation reaction at a very rapid rate (28 400 M −1 s −1 ). The CBOA-based photo-click reaction was proved to be bioorthogonal. In addition, the NoxaB peptide was successfully cross-linked by a CBOA stapler which plays a dual role: photo-control of the conformation of the peptide and photo-conjugation of probes in live cells.